Diagnostic Challenge in a Patient with Severe Anion Gap Metabolic Acidosis - Eugene M. Tan; Ejaaz Kalimullah; M. Rizwan Sohail; Kannan Ramar (Case Reports in Critical Care)
The approach to the patient with acute renal failure and elevated anion and osmolal gap is difficult. Differential diagnoses include toxic alcohol ingestion, diabetic or starvation ketoacidosis, or 5-oxoproline acidosis. We present a 76-year-old female with type 2 diabetes mellitus, who was found at home in a confused state. Laboratory analysis revealed serum pH 6.84, bicarbonate 5.8 mmol/L, pCO2 29 mmHg, anion gap 22.2 mmol/L, osmolal gap 17.4 mOsm/kg, elevated beta-hydroxybutyrate (4.2 mmol/L), random blood sugar 213 mg/dL, creatinine 2.1 mg/dL, and potassium 7.5 mmol/L with no electrocardiogram (EKG) changes. Fomepizole and hemodialysis were initiated for presumed ethylene glycol or methanol ingestion. Drug screens returned negative for ethylene glycol, alcohols, and acetaminophen, but there were elevated urine levels of acetone (11 mg/dL). The acetaminophen level was negative, and 5-oxoproline was not analyzed. After 5 days in the intensive care unit (ICU), her mental status improved with supportive care. She was discharged to a nursing facility. Though a diagnosis was not established, our patient’s presentation was likely due to starvation ketosis combined with chronic acetaminophen ingestion. Acetone ingestion is less likely. Overall, our case illustrates the importance of systematically approaching an elevated osmolal and anion gap metabolic acidosis.